DELEUZE, A STOIC - Johnson, Ryan J. (Plateaus., 2020)
Ryan Johnson reveals that Deleuze's provocative reading of ancient Stoicism produced many of his most singular and powerful ideas. Including previously untranslated French Stoic scholarship, Johnson unearths new possibilities for bridging contemporary and ancient philosophy.